DIFFERENT APPROACHES TO PROPER NAMES IN LINGUISTICS - Бахтиёрова, М.Б. (FAN va JAMIYAT, 2022)
The article discusses the general theoretical problems in the field of studying the general problems of proper names in linguistics. In particular, the differences between proper names and common names are shown on the basis of theories given by famous linguists, in linguistics information about the emergence of the approach to proper names from an abstract-logical and concrete-historical point of view. The article analyzes the assumption that the names of people and things are assimilated from their inherent natures, especially with emphasis on important features in their natures. Hence, it is concluded that even in the modern culture of many countries, proper names have retained a certain meaning for their owners.